A comparative study of primary cellulitis and its local complications in lower limbs in diabetics and non-diabetics through the new Amit Jain’s staging system from India - P. B., Sharada; Krishnappa, Rohit; Jain, Amit Kumar C.; Ramachandra, Hariprasad Taluru (International Surgery Journal, 2020)
Background: The objective of the study was to validate Amit Jain’s staging system for cellulitis in diabetic and non-diabetic lower limbs and to predict the outcomes associated with cellulitis and surgical procedures done in them. Methods: We conducted a prospective study in department of surgery at Raja Rajeswari Medical College and Hospital Bengaluru, India. The study period was from December 2018 to November 2019. Statistical analysis was done using SPSS 22 and R environment ver.3.2.2. Results: A total of 36 patients were included in this study of which 21 were diabetics and were in placed in group A and 15 were non diabetics and placed in group B. 83.3% of the patients were males. 73.3% of non-diabetics had stage 1 cellulitis and 33.3% of diabetics had stage 1 and 2 each. 47.2% of patients underwent debridement and it was significantly common in diabetics (p=0.037) and also it was common in higher stages of cellulitis (p=0.001). 8.3% had amputation in this series. All the major amputations were done in stage 4 cellulitis (p=0.002). Conclusions: In this validation study, it can be seen that cellulitis is common in both diabetics and non-diabetics but it is severe in diabetic patients. Stage 3 was more common in diabetics compared to non-diabetics. Amit Jain’s staging system of cellulitis is a simple, easy, practical, focal classification that guides therapy and predicts amputation.